PENGARUH EDUKASI DIET DASH (DIETARY APPROACHES TO STOP HYPERTENSION) METODE PEER GROUP TERHADAP POLA MAKAN PENDERITA HIPERTENSI DI DESA KETOMPEN - Himmatul Azdimah; Dodik Hartoni; Nafolion Nur Rahmat (JOURNAL SAINS STUDENT RESEARCH, 2025)
Diet is the most important behavior that can affect nutritional conditions. The DASH diet is a diet of vegetables and fruits that contain lots of dietary fiber (30 grams / day) and minerals (potassium, magnesium and calcium) while salt intake is limited. The purpose of the study was to analyze the effect of DASH Diet Education (Dietary Approaches to Stop Hypertension) Peer Group Method on the Diet of Hypertension Patients. The method in this study used pre-experimental design research with one group pre and post-test design. The population was 50, and the sample was 44 respondents with purposive sampling technique. Educational interventions were carried out in 3 meetings which included pretest, provision of DASH diet education peer group method, and post-test. The instrument used was a dietary questionnaire with indicators of meal frequency, amount of food, and type of food. Data obtained is with Wilcoxon signed rank test.The results of the study obtained a diet before the DASH Diet Education intervention showed the results in the pretest majority of the sufficient category, about 23 respondents (52.3%). In the post test data after being given education, the majority of the results were in the good category, namely 22 respondents (50.0%). The statistical test results obtained P value = 0.000 so, there was an effect of DASH Diet Education Peer Group Method on the Diet of Hypertension Patients.DASH diet education through a peer group approach is able to improve diet in patients with hypertension. The peer group method is proven to support the learning process because of the discussion and sharing of experiences between respondents, which makes the material easier to understand and apply in everyday life.